A Conceptual Pattern for Ranking Urban Furniture in Pedestrian Pathways of Tabriz from a Socio-Cultural Perspective (Case Study: Ark, Maqsudiyeh, Tarbiat, and Valiasr Pathways) - Afrang Beignejad Heric; Reza Valizadeh; Ali Panahi (اکولوژی انسانی, 2025)
This study aims to present a conceptual model for ranking urban furniture in the pedestrian pathways of Ark, Maqsudiyeh, Tarbiat, and Valiasr in the city of Tabriz. Urban furniture, as a fundamental element of public spaces, plays a vital role in enhancing quality of life, fostering social interaction, and attracting tourists. The research employs a mixed-method approach. In the quantitative phase, data were collected through questionnaires completed by 20 urban experts and analyzed using Shannon Entropy and TOPSIS techniques. In the qualitative phase, semi-structured interviews with professionals were conducted and analyzed using content analysis.Findings revealed that Valiasr pedestrian pathway ranked first with a similarity index of 0.822 due to its environmental coherence, design quality, and user comfort. Tarbiat ranked second with an index of 0.751, benefiting from well-planned design and accessibility to services. The Ark and Maqsudiyeh pathways ranked third and fourth with indices of 0.627 and 0.548 respectively, reflecting deficiencies in urban furniture and a lack of environmental integration. The proposed conceptual model includes four key components: design and identity, application of smart technologies, creation of social spaces, and ensuring pedestrian safety.This research highlights the significant impact of urban furniture on the performance of pedestrian pathways, and the proposed model offers a comprehensive framework for enhancing the quality and attractiveness of urban pedestrian areas in Tabriz and other cities.